A study of otolaryngology resident quality of life and sleepiness. Issue 3 (10th March 2017) - Garcia‐Rodriguez, Laura R.; Sanchez, Dominique L.; Ko, Alvin B.; Williams, Amy M.; Peterson, Ed; Yaremchuk, Kathleen L.
Abstract : Objectives: This study aimed to determine otolaryngology residents' quality of life and sleepiness. Methods: An electronic survey was distributed to otolaryngology residents in the United States in October 2014 and May 2015. The survey included questions from the Physician Well‐Being Index (PWBI) and Epworth Sleepiness Scale (ESS). Data were analyzed using standard descriptive and frequency analyses, Spearman correlations, and Student's t‐test. Results: The 196 respondents (13% response rate) had a mean age of 29.9 years and worked an average of 70.88 hours/week. Higher PWBI score (lower quality of life) correlated with higher ESS (more sleepiness) for all respondents regardless of rotation (Spearman coefficient of .45; p = .001). PWBI scores were higher for head/neck oncology. Both PWBI and ESS scores were highest for postgraduate year two. PWBI showed a significant positive correlation with hours worked (correlation coefficient .35; p = .001) as well as a significant negative correlation with exercise time (correlation coefficient ‐.18; p = .010). There was a positive correlation between hours worked and ESS (correlation coefficient .48; p = .001). Conclusion: For the otolaryngology survey respondents, sleepiness and overall well‐being were better during the first year with a dramatic worsening during junior years followed by an improvement in the senior years. More work hours and poor quality of life was associated with less physically active residents. Focused interventions during these rotations may reduce distress, improve quality of life, and enhance learning. Level of Evidence: NA